Study skills for your masters in teaching and learning - Castle, Karen (Exeter : Learning Matters, 2010)
A practical guide for all teachers embarking on their Masters in Teaching and Learning (MTL). It begins by encouraging the reader to identify their own learning style and engage in different study methods, and goes on to explore higher level study skills and academic writing.
Theories, models and learning styles -- Developing higher-level study skills -- Developing higher-level academic writing skills -- Introduction to research -- Research methodologies -- Developing critical and analytical writing skills -- Assessment -- The practicalities of studying in the twenty-first century.
Incluye referencias bibliográficas e índice.
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Recurso electrónico. Santa Fe, Arg.: elibro, 2020. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Education -- Study and teaching (Graduate) -- Great Britain; Study skills; Libros electrónicos.